A Decolonial Imagination: Sociology, Anthropology and the Politics of Reality. (February 2017) - Savransky, Martin
While the recent proliferation of sociological engagements with postcolonial thought is important and welcome, central to most critiques of Eurocentrism is a concern with the realm of epistemology, with how sociology comes to know its objects of study. Such a concern, however, risks perpetuating another form of Eurocentrism, one that is responsible for instituting the very distinction between epistemology and ontology, knowledge and reality. By developing a sustained engagement with Boaventura de Sousa Santos's work, as well as establishing possible connections with what has been termed the 'turn to ontology' in anthropology, in this article I argue that in order for sociology to become exposed to the deeply transformative potential of non-Eurocentric thinking, it needs to cultivate a decolonial imagination that may enable it to move beyond epistemology, and to recognise that there is no social and cognitive justice without existential justice, no politics of knowledge without a politics of reality.